Effect of different fly ash ratios on the mechanical properties of hybrid steel fiber reinforced concrete - Kaya, Necim (Frontiers in Materials, 2025)
This study explores the influence of varying proportions (5%, 15%, and 25%) of Class F fly ash on the mechanical properties of hybrid steel fiber-reinforced concrete (HSFRC). Concrete mixtures were prepared with fixed total steel fiber content (1% by volume) using micro and macro fibers in specific ratios. Portland cement was partially replaced by fly ash, and slump, compressive, flexural, and splitting tensile strength tests were conducted at 7, 28, and 90 days according to TS EN and ASTM standards. The results showed that while early-age strength decreased due to the slow pozzolanic activity of fly ash, the mixture containing 15% fly ash consistently provided the best mechanical performance at 90 days, reaching a compressive strength of 81 MPa. These findings confirm that 15% fly ash is an optimal replacement level for long-term strength development in HSFRC. The study also emphasizes the economic and environmental benefits of incorporating fly ash in concrete production.